Source material for breeding spring barley cultivars with high grain quality - I. Yu. Zaytseva; I. N. Shchennikova; E. M. Lisitsyn (Труды по прикладной ботанике, генетике и селекции)
Background. The problem of improving barley (Hordeum vulgare L.) grain quality, in particular grain protein content, is of practical importance for breeding.   The objective was to select high-protein genetic sources of spring barley for breeding new cultivars and search for possibilities of predicting grain protein content according to the chlorophyll content in leaves.   Materials and methods. The studies were conducted in 2018–2020 on 28 barley genotypes of different ecogeographic origin in accordance with conventional methods. Grain protein content was assessed using near-infrared spectroscopy, and chlorophyll content was measured spectrophotometrically in acetone leaf extracts using the method: Chlorophylls and carotenoids: measurement and characterization by UV-VIS spectroscopy.   Results and conclusion. Average grain protein content significantly correlated with the amount of precipitations (r = 0.67), the sum of effective temperatures (r = 0.75) and the hydrothermal coefficient (r = 0.76) during the growing season. Genotypes with high grain protein content, high test weight, and grain uniformity were selected. Accessions k-30574 and k-30256 showing high yields and resistance to lodging are promising for the development of high-protein cultivars. Accessions k-15619, k-30379 and k-31046 demonstrated high plasti city in their protein content parameters. Accession k-5983 was characterized by consistently high grain protein content. Statistically significant correlations between chlorophyll content in the flag leaf and grain protein content were found in a set of accessions with environmental plasticity (bi) values lower than 1.0 (r = 0.585…–0.645). A decrease in protein content was observed in extensive-type accessions with increased pigment content in leaves (r = –0.643 and –0.638 for Chl a and Chl b, respectively; r = –0.645 for the total chlorophyll). A high Chl a/b ratio may serve as an indicator of higher grain protein content levels in such genotypes (r = 0.585).